2020
DOI: 10.1002/ca.23713
|View full text |Cite
|
Sign up to set email alerts
|

The series of smooth muscle structures in the pelvic floors of men: Dynamic coordination of smooth and skeletal muscles

Abstract: Introduction Recent studies have revealed the extended nature of smooth muscle structures in the pelvic floor, revising the conventional understanding of the “perineal body.” Our aim was to clarify the three‐dimensional configuration and detailed histological properties of the smooth muscle structures in the region anterior to the rectum and anal canal in men. Materials and methods Four male cadavers were subjected to macroscopic and immunohistological examinations. The pelvis was dissected from the perineal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 33 publications
(72 reference statements)
1
24
0
Order By: Relevance
“…It is interesting that the seemingly unrelated EAS, STP, and LA surround the CG while extending anteromedially. In contrast, the DTP was observed as a plate-like structure of smooth muscle located in the deep perineal pouch, in agreement with our recent report 11,16 . In the present study, we showed that the DTP surrounds the medial and posterosuperior parts of the CG.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…It is interesting that the seemingly unrelated EAS, STP, and LA surround the CG while extending anteromedially. In contrast, the DTP was observed as a plate-like structure of smooth muscle located in the deep perineal pouch, in agreement with our recent report 11,16 . In the present study, we showed that the DTP surrounds the medial and posterosuperior parts of the CG.…”
Section: Discussionsupporting
confidence: 92%
“…The DTP is a mysterious muscle; while there are reports that it does not exist 24,25 , www.nature.com/scientificreports/ some reports state that it is seen in 24.7%-100% of men and 16.7% of women 8,10,[26][27][28] . The DTP is classically considered to be comprised striated muscle 4 ; however, recent reports have indicated that it is comprised smooth muscle that traverses in the deep perineal pouch 11,16,[29][30][31][32] . The present study showed that the EUS surrounds the anterior and lateral sides of the urethra, and is formed from muscle bundles of the STPs, LA, and EAS extending into the deep perineal pouch.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations